Gott im Quartier (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
The contributions in this volume shed light on the dimension of spirituality in the churches' orientation towards social spaces, going beyond a narrow social work approach and respecting the autonomy and self-determination of those involved. Social spaces are understood as spiritual spaces of experience in which forms of self-transcendence are made possible and in which people can encounter God. Subsequently, the religious topography of urban neighbourhoods and possible sacred spatial experiences in church buildings and landscapes are examined. Finally, individual contributions focus on actors in social space who can cooperatively contribute to its design and thus realise cooperative principles. Experiences of segregation in cities come into play here. With contributions by Martina Bär | Julia Beideck | Ulrich Beuttler | Bert Daelemans | Frank Eckhardt | Felix Eiffler | Johannes Eurich | Sonja Keller | Anna Körs | Olaf Kühne | Georg Lämmlin | Andreas Lob-Hüdepohl | Sabrina Müller | Frank Schultz-Nieswandt | Claudia Schulz | Philip Thimm | Gerhard Wegner